Penerapan Metode Diskusi pada Pembelajaran Pendidikan Agama Islam untuk Membangun Semangat Belajar Siswa Kelas XI di SMA Mandala Trikora Jayapura - Lanang Aqsal Syahputra; Hasruddin Dute; Moh. Ali Mahmudi; Muh. Abdul Mukti (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2022)
This study aims to obtain an overview of the application of the discussion method in Islamic Religious Education learning for class XI students at SMA Mandala Trikora Jayapura, and to determine the impact of the application of this method on students' learning enthusiasm. The discussion method is seen as one of the learning strategies that can encourage active involvement of students in the learning process, so it is expected to increase student participation, understanding, and learning motivation in following Islamic Religious Education learning in class. This study uses a qualitative approach with the researcher as the main instrument. The data sources in this study consist of primary data obtained from Islamic Religious Education teachers and class XI students of SMA Mandala Trikora Jayapura, as well as secondary data derived from various relevant references such as books, scientific journals, theses, and other supporting documents. Data collection techniques are carried out through observation, interviews, and documentation. The validity of the data is tested through credibility, transferability, dependability, and confirmability tests. Meanwhile, data analysis techniques are carried out through the stages of data reduction, data presentation (data display), and verification or drawing conclusions. The results of the study indicate that Islamic Religious Education learning at SMA Mandala Trikora Jayapura has implemented the discussion method as one of the learning strategies. This method is implemented through three stages: preparation, implementation, and evaluation. During the implementation stage, the teacher first provides an explanation to students, then randomly divides them into groups to discuss the material presented. The implementation of the discussion method has had positive impacts, including increased student engagement with peers and the teacher, increased self-confidence in expressing opinions, and improved speaking skills in front of peers. However, some challenges arise, such as some students being less active in thinking and discussing, resulting in passive participation in group activities.